Analisis Struktur dan Nilai Teks Mitos Sang Naga Rarik di Pura Luhur Mekori - Dewi Kartika Sari, Ni Luh Putu; Rai Putra, Ida Bagus; Mulyawati R,, Tjok. Istri Agung (Humanis; Vol 24 No 4 (2020)DO - 10.24843/JH.2020.v24.i04.p10, 2020)
This study aims to examine the Mythical Texts of the Dragons Rarik in Luhur Mekori Temple, Belimbing Village, Pupuan District, Tabanan Regency Structure and Value Analysis. The purpose of this study is to describe the narrative structure that builds this mythical text and find out what values ??are contained in it. This study using two theories namely, structural theory and value theory. The methods and techniques used in this study consist of three stages, namely Methods and Techniques of providing data using observation and interview methods that assisted by recording techniques and translation techniques. Methods and data analysis techniques using qualitative methods with descriptive analytic techniques. Methods and Techniques of presenting the results of data analysis using informal methods supported by inductive and deductive techniques. The results that can be obtained in this study are the narrative structure that builds the mythical texts of the Naga Rarik in Pura Luhur Mekori, specifically incidents, plots, character and characterization, setting themes, and mandates. Besides, this study also knows the values ??contained in this mythical text, namely religious values ??(magical values ??and belief values), and ethical values.